Solved and unsolved riddles about low-latitude daytime valley region plasma waves and 150-km echoes - Chau, J. L.; Longley, W. J.; Reyes, P. M.; Pedatella, N. M.; Otsuka, Y.; Stolle, C.; Liu, H.; England, S. L.; Vierinen, J. P.; Milla, M. A.; Hysell, D. L.; Oppenheim, M. M.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
The Earth's atmosphere near both the geographic and magnetic equators and at altitudes between 120 and 200 km is called the low-latitude valley region (LLVR) and is among the least understood regions of the ionosphere/thermosphere due to its complex interplay of neutral dynamics, electrodynamics, and photochemistry. Radar studies of the region have revealed puzzling daytime echoes scattered from between 130 and 170 km in altitude. The echoes are quasi-periodic and are observed in solar-zenith-angle dependent layers. Populations with two distinct types of spectral features are observed. A number of radars have shown scattering cross-sections with different seasonal and probing-frequency dependencies. The sources and configurations of the so-called 150-km echoes and the related irregularities have been long-standing riddles for which some solutions are finally starting to emerge as will be described in this review paper. Although the 150-km echoes were discovered in the early 1960s, their practical significance and implications were not broadly recognized until the early 1990's, and no compelling explanations of their generation mechanisms and observed features emerged until about a decade ago. Now, more rapid progress is being made thanks to a multi-disciplinary team effort described here and recent developments in kinetic simulations and theory: 18 of 27 riddles to be described in this paper stand solved (and a few more partially solved) at this point in time. The source of the irregularities is no longer a puzzle as compelling evidence has emerged from simulations and theory, presented since 2016 that they are being caused by photoelectrons driving an upper hybrid plasma instability process. Another resolved riddle concerns the persistent gaps observed between the 150-km scattering layers --- we now understand that they are likely to be the result of enhanced thermal Landau damping of the upper hybrid instability process at upper hybrid frequencies matching the harmonics of the electron gyrofrequency. The remaining unsolved riddles, e.g., minute-scale variability, multi-frequency dependence, to name a few, are still being explored observationally and theoretically --- they are most likely unidentified consequences of interplay between plasma physics, photochemistry, and lower atmospheric dynamic processes governing the LLVR.